THE USE OF THE PROJECT METHOD TO DEVELOP STUDENTS' INFORMATION COMPETENCE - Ilyasova Zukhra Kenesbayevna (International Journal on Human-Computing Studies, 2021)
The state describes the application of the project methodology for the formation of information competence of students in the system of pedagogicalhigher education. It defines the requirements and objectives in terms of knowledge, intelligence and skills that students must be in mastering the subject.